Evidence of interpersonal violence or a special funeral rite in the Neolithic multiple burial from Koszyce in southern Poland – a forensic analysis - Konopka, Tomasz; Szczepanek, Anita; Przybyła, Marcin M.; Włodarczak, Piotr (Anthropological Review, 2016)
This study uses anthropological and forensic medical analyses to determine the cause of fractures found in the remains of 15 individuals buried at a site associated with the Globular Amphora Culture (2875-2670 BC). The intent was to determine the mechanism underlying the injuries and to indicate the types of tools that might have inflicted the blows. The fractures were diversified in their forms, but the majority of the injuries appear to have been inflicted by a flint axe, which is frequently found in graves of the Globular Amphora Culture. Apart from the forearm being severed in one of the victims, all the remaining skeletons showed from 1 to 4 injuries involving solely the skulls. The grave might contain victims attacked by invaders who executed the captives, or else the feature is ritual in character and it reflects the beliefs of the Neolithic community.